Hubungan Pemahaman Teori dan Fasilitas Kerja terhadap Prestasi Praktek Pengefraisan Kelas XI Teknik Permesinan SMK Negeri 1 Lembah Melintang - Rizaldi, Ahmad; Purwantono, Purwantono; Syahri, Budi; Abadi, Zainal (Lembaga Yasin AlSys, 2025)
This study aims to determine the relationship between the understanding of milling machining theory and work facilities on the practical performance of eleventh-grade students in the Machining Engineering program at SMK Negeri 1 Lembah Melintang. The method used in this study is quantitative with a correlational approach. Data were collected through observation, documentation, and the distribution of questionnaires, then analyzed using simple regression and multiple regression. The results indicate a positive relationship between the understanding of milling machining theory and practical performance in milling machining, with a correlation coefficient of 0.357. Work facilities also show a positive relationship with practical performance, with a correlation coefficient of 0.242. Additionally, the results of the multiple regression analysis indicate that the understanding of milling machining theory and work facilities together positively relate to practical performance in milling machining, with a correlation coefficient of 0.402. The effective contribution of both variables to practical performance is 16%, with a relative contribution of understanding theory at 11.5% and work facilities at 4.5%. These findings suggest that improving theoretical understanding and providing adequate work facilities can enhance students' practical performance in milling.